2018
DOI: 10.3389/fendo.2018.00680
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Air Pollution: Effects on the Cardiovascular System

Abstract: Air pollution is a complex mixture of gaseous and particulate components, each of which has detrimental effects on human health. While the composition of air pollution varies greatly depending on the source, studies from across the world have consistently shown that air pollution is an important modifiable risk factor for significantly increased morbidity and mortality. Moreover, clinical studies have generally shown a greater impact of particulate matter (PM) air pollution on health than the gaseous component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
318
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 470 publications
(332 citation statements)
references
References 217 publications
(232 reference statements)
5
318
1
8
Order By: Relevance
“…Although ultrafine particles contribute only to a small fraction of the total ambient PM mass, they are typically present in high concentrations in the urban atmosphere (3,(29)(30)(31) and have a high probability to deposit in the pulmonary system after inhalation than large particles (32,33). Through blood circulation and endocytosis, ultrafine particles likely enter organs beyond the lungs, such as the reproductive tract, heart, liver, spleen, kidneys, brain, and BAT (34,35). The large surface area, high redox capacity, and ability to form radical species for ultrafine particles likely induce inflammatory effects, cause cellular DNA damage, and interfere with cell metabolism and function (27,36).…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrafine particles contribute only to a small fraction of the total ambient PM mass, they are typically present in high concentrations in the urban atmosphere (3,(29)(30)(31) and have a high probability to deposit in the pulmonary system after inhalation than large particles (32,33). Through blood circulation and endocytosis, ultrafine particles likely enter organs beyond the lungs, such as the reproductive tract, heart, liver, spleen, kidneys, brain, and BAT (34,35). The large surface area, high redox capacity, and ability to form radical species for ultrafine particles likely induce inflammatory effects, cause cellular DNA damage, and interfere with cell metabolism and function (27,36).…”
Section: Discussionmentioning
confidence: 99%
“…The main underlying cause of cardiovascular diseases is atherosclerosis, which is recognized as a chronic inflammatory disease [4]. Evidence has indicated that exposure to PM air pollution elicits numerous pathological and biological responses, including systemic inflammation and oxidants, which increases the relative risk of cardiovascular mortality [2,[5][6][7]. Although the toxic effects of PM on cardiovascular disease are usually assessed by its particle mass, there is increasing evidence that the chemical composition and size/morphology of PM may be a major contributor to its pathotoxicity toward the cardiovascular system [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact biological pathways underlying the cardiovascular health effects of PM inhalation remain largely debatable, both oxidative stress and systemic inflammation have been purported to play major independent and interactive roles (Hamanaka & Mutlu, ). PM‐induced oxidative stress has been shown to activate the autonomic nervous system, producing a sympathetic response involving adverse physiological changes (e.g., hypertension and impaired heart rate variability [HRV]) which can compromise cardiovascular health (Hamanaka & Mutlu, ; Morishita, Thompson, & Brook, ). Ambient PM exposure has also been shown to be associated with an immunological response involving the release of proinflammatory cytokines, such as CRP, IL‐6 (Du et al, ; Hamanaka & Mutlu, ; Ridker, Hennekens, Buring, & Rifai, ; Shrivastava, Singh, Raizada, & Singh, ), and other types of immune cells (e.g., white blood cells) circulating within the blood (Steenhoff et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…PM‐induced oxidative stress has been shown to activate the autonomic nervous system, producing a sympathetic response involving adverse physiological changes (e.g., hypertension and impaired heart rate variability [HRV]) which can compromise cardiovascular health (Hamanaka & Mutlu, ; Morishita, Thompson, & Brook, ). Ambient PM exposure has also been shown to be associated with an immunological response involving the release of proinflammatory cytokines, such as CRP, IL‐6 (Du et al, ; Hamanaka & Mutlu, ; Ridker, Hennekens, Buring, & Rifai, ; Shrivastava, Singh, Raizada, & Singh, ), and other types of immune cells (e.g., white blood cells) circulating within the blood (Steenhoff et al, ). Key biological markers, including CRP, Amyloid A, and IL‐6, have been used as nonspecific measures of inflammatory status in epidemiologic studies of CVD in women (Ridker et al, ; Shrivastava et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation